Conditional cash transfers : reducing present and future poverty - Fiszbein, Ariel (World Bank policy research report., 2009)
Conditional Cash Transfer (CCT) programs aim to reduce poverty by making welfare programs conditional upon the receivers' actions. That is, the government only transfers the money to persons who meet certain criteria. These criteria may include enrolling children into public schools, getting regular check-ups at the doctor's office, receiving vaccinations, or the like. They have been hailed as a way of reducing inequality and helping households break out of a vicious cycle whereby poverty is transmitted from one generation to another. Do these and other claims make sense? Are they supported by.